HCV Infection Increases the Expression of ACE2 Receptor, Leading to Enhanced Entry of Both HCV and SARS-CoV-2 into Hepatocytes and a Coinfection State - Tom Domovitz; Samer Ayoub; Michal Werbner; Joel Alter; Lee Izhaki Tavor; Yfat Yahalom-Ronen; Evgeny Tikhonov; Tomer Meirson; Yaakov Maman; Nir Paran; Tomer Israely; Moshe Dessau; et al. (Microbiology Spectrum, 2022)
ABSTRACT Recent studies suggest the enhancement of liver injury in COVID-19 patients infected with Hepatitis C virus (HCV). Hepatocytes express low levels of angiotensin-converting enzyme 2 (ACE2), the SARS-CoV-2 entry receptor, raising the possibility of HCV-SARS-CoV-2 coinfection in the liver. This work aimed to explore whether HCV and SARS-CoV-2 coinfect hepatocytes and the interplay between these viruses. We demonstrate that SARS-CoV-2 coinfects HCV-infected Huh7.5 (Huh7.5HCV) cells. Both viruses replicated efficiently in the coinfected cells, with HCV replication enhanced in coinfected compared to HCV-mono-infected cells. Strikingly, Huh7.5HCV cells were eight fold more susceptible to SARS-CoV-2 pseudoviruses than naive Huh7.5 cells, suggesting enhanced SARS-CoV-2 entry into HCV-preinfected hepatocytes. In addition, we observed increased binding of spike receptor-binding domain (RBD) protein to Huh7.5HCV cells, as well as enhanced cell-to-cell fusion of Huh7.5HCV cells with spike-expressing Huh7.5 cells. We explored the mechanism of enhanced SARS-CoV-2 entry and identified an increased ACE2 mRNA and protein levels in Huh7.5HCV cells, primary hepatocytes, and in data from infected liver biopsies obtained from database. Importantly, higher expression of ACE2 increased HCV infection by enhancing its binding to the host cell, underscoring its role in the HCV life cycle as well. Transcriptome analysis revealed that shared host signaling pathways were induced in HCV-SARS-CoV-2 coinfection. This study revealed complex interactions between HCV and SARS-CoV-2 infections in hepatocytes, which may lead to the increased liver damage recently reported in HCV-positive COVID-19 patients. IMPORTANCE Here, we provide the first experimental evidence for the coexistence of SARS-CoV-2 infection with HCV, and the interplay between them. The study revealed a complex relationship of enhancement between the two viruses, where HCV infection increased the expression of the SARS-CoV-2 entry receptor ACE2, thus facilitating SARS-CoV-2 entry, and potentially, also HCV entry. Thereafter, SARS-CoV-2 infection enhanced HCV replication in hepatocytes. This study may explain the aggravation of liver damage that was recently reported in COVID-19 patients with HCV coinfection and suggests preinfection with HCV as a risk factor for severe COVID-19. Moreover, it highlights the possible importance of HCV treatment for coinfected patients. In a broader view, these findings emphasize the importance of identifying coinfecting pathogens that increase the risk of SARS-CoV-2 infection and that may accelerate COVID-19-related co-morbidities.